Effects of erythropoietin on fibroblast growth factor 23 in mice and humans. Issue 12 (10th July 2018) - Hanudel, Mark R; Eisenga, Michele F; Rappaport, Maxime; Chua, Kristine; Qiao, Bo; Jung, Grace; Gabayan, Victoria; Gales, Barbara; Ramos, Georgina; de Jong, Maarten A; van Zanden, Jelmer J; de Borst, Martin H; et al.
Abstract: Background: Erythropoietin (EPO) has been reported as a novel determinant of fibroblast growth factor 23 (FGF23) production; however, it is unknown whether FGF23 is stimulated by chronic exposure to EPO or by EPO administration in nonpolycystic chronic kidney disease (CKD) models. Methods: We analyzed the effects of chronic EPO on FGF23 in murine models with chronically high EPO levels and normal kidney function. We studied the effects of exogenous EPO on FGF23 in wild-type mice, with and without CKD, injected with EPO. Also, in four independent human CKD cohorts, we evaluated associations between FGF23 and serum EPO levels or exogenous EPO dose. Results: Mice with high endogenous EPO have elevated circulating total FGF23, increased disproportionately to intact FGF23, suggesting coupling of increased FGF23 production with increased proteolytic cleavage. Similarly, in wild-type mice with and without CKD, a single exogenous EPO dose acutely increases circulating total FGF23 out of proportion to intact FGF23. In these murine models, the bone marrow is shown to be a novel source of EPO-stimulated FGF23 production. In humans, serum EPO levels and recombinant human EPO dose are positively and independently associated with total FGF23 levels across the spectrum of CKD and after kidney transplantation. In our largest cohort of 680 renal transplant recipients, serum EPO levels are associated with total FGF23, but not intact FGF23, consistent with the effects of EPO on FGF23 production and metabolism observed in our murine models. Conclusion: EPO affects FGF23 production and metabolism, which may have important implications for CKD patients.